2013
DOI: 10.1111/nure.12065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chocolate on cognitive function and mood: a systematic review

Abstract: A systematic review was conducted to evaluate whether chocolate or its constituents were capable of influencing cognitive function and/or mood. Studies investigating potentially psychoactive fractions of chocolate were also included. Eight studies (in six articles) met the inclusion criteria for assessment of chocolate or its components on mood, of which five showed either an improvement in mood state or an attenuation of negative mood. Regarding cognitive function, eight studies (in six articles) met the crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 95 publications
(195 reference statements)
4
69
1
3
Order By: Relevance
“…This review concluded that there are measurable neurocognitive effects with acute administration of cocoa flavanols, caffeine, and theobromine, in isolation and in combination, and suggested that some effects of chocolate and chocolate components could be due to attenuation of negative mood. Furthermore, the review pointed out that the dosing periods of the enrolled studies varied from 5 days to 6 weeks, and it was hypothesized that the lack of positive outcomes was related to possible methodological limitations [29]. Three other randomized controlled trials were published after this systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review concluded that there are measurable neurocognitive effects with acute administration of cocoa flavanols, caffeine, and theobromine, in isolation and in combination, and suggested that some effects of chocolate and chocolate components could be due to attenuation of negative mood. Furthermore, the review pointed out that the dosing periods of the enrolled studies varied from 5 days to 6 weeks, and it was hypothesized that the lack of positive outcomes was related to possible methodological limitations [29]. Three other randomized controlled trials were published after this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that 3 out of the 8 studies that met the criteria for inclusion revealed evidence for cognitive enhancement following cocoa flavanols and methylxanthine intake [29]. All studies examined the cognitive effects of potentially psychoactive fractions of chocolate: 5 studies focused on cocoa flavanol fractions of cocoa [5][6][7]9, 10] and 3 (from two articles) on combinations of the methylxanthines, caffeine, and theobromine [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rafnsson et al 2013 [24] Systematic review III-3 Two dietary intake studies of 342 and 1640 elderly participants for 3 and 10 years assessing the effects of flavonoids on cognitive decline, found a lower rate of cognitive decline with increased intake and no association respectively. Scholey and Owen 2013 [26] Systematic review II One RCT of 101 participants, ≥ 60 years of age and 6 weeks duration found no difference in cognitive performance following consumption of a chocolate bar (397mg proanthocyanins) and cocoa drink (357mg proanthocyanins) compared to placebo. …”
Section: Polyphenolsmentioning
confidence: 99%
“…También hay evidencias del efecto beneficioso de ciertos nutrientes como la vitamina D y los flavonoides sobre el estado mental (9)(10)(11). El chocolate es un alimento con gran contenido en flavonoides y metilxantinas.…”
Section: Introductionunclassified